Les Normes de Prononciation du Français : Une étude Perceptive Panfrancophone. - Chalier, Marc. (Beihefte Zur Zeitschrift Für Romanische Philologie Series, 2021)
The book series Beihefte zur Zeitschrift für romanische Philologie is among the most renowned publications in Romance Studies. It covers the entire field of Romance linguistics, including the national languages as well as the lesser studied Romance languages. The series publishes high-quality monographs and collected volumes on all areas of linguistic research, on medieval literature and on textual criticism.